Collaborative Practical Theology Engaging Practitioners in Research on Christian Practices - de Roest, Henk (Theology in Practice, 2019)
In Collaborative Practical Theology, Henk de Roest documents and analyses research on Christian practices as it can be conducted by academic practical theologians in collaboration with practitioners of different kinds in Christian practices all around the world.; Readership: Theological institutes worldwide, academic libraries, researchers in Practical Theology, practitioners, students, consultants, everyday believers, all interested in Christian practices.